International humanitarian law - Jan, Mohammad Naqib Ishan; Haruna, Abdulrashid Lawan (IIUM Press, 2015)
This book is written not because of any foreseen break of armed conflict, but armed conflict is an inevitable phenomenon in human and international relations since despite the United Nations Charter prohibition on the use of force in international relations, war still exist. Hence, there is need to have law that regulates conduct in time of armed conflict. International humanitarian law (IHL) being the law of armed conflict has to be disseminated to the entire society through a comprehensive medium that everyone can understand and appreciate.